2015
DOI: 10.1016/j.proenv.2015.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Academic Fit, Adolescent-parent Career Congruence, and Career Exploration in University Students

Abstract: Based on the person-environment congruence theory which argues that better fit with individual's environment will lead to more positive outcomes, we examined the relationships between the fit between individuals and organization (i.e., academic fit), the fit between individuals and their parents (i.e., adolescent-parent career congruence), and career exploration in Indonesian university students. We surveyed 125 students (53.6% girls, mean age = 18.96 years) majoring in Fisheries and Marine Science from a stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 15 publications
2
13
0
1
Order By: Relevance
“…Our work enriches the applicable case of the PWT model. Second, previous studies have identified several perceptions variables that impact career exploration behavior [60,61]; our work contributed another vital antecedent of career exploration behavior, namely future decent work perceptions. The positive relationship between the two factors sheds some light on the future managerial practices which will be discussed in the coming session.…”
Section: Contributions Implications and Future Research Directionsmentioning
confidence: 81%
See 3 more Smart Citations
“…Our work enriches the applicable case of the PWT model. Second, previous studies have identified several perceptions variables that impact career exploration behavior [60,61]; our work contributed another vital antecedent of career exploration behavior, namely future decent work perceptions. The positive relationship between the two factors sheds some light on the future managerial practices which will be discussed in the coming session.…”
Section: Contributions Implications and Future Research Directionsmentioning
confidence: 81%
“…In addition to the personal beliefs mentioned above, perceptions in general and psychological ones in particular, tend to have an impact on one's career exploration [60,61]. Studies show that college students' views on their academic fitness and the consistency between their own career expectations and those of their parents lead them to participate more in career exploration activities [60].…”
Section: Linking Decent Work Perceptions With Career Explorationmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism of attaining career satisfaction should be attained from the childhood; since this period, the career satisfaction should be explored by means of stimulation toward career introduction in the kindergarten. Career exploration thus refers to the activities of gathering relevant information with regards to the progress of individual career (Sawitri & Dewi, 2015). Furthermore, (Denault, Ratelle, Duchesne, & Guay, 2019) states that career exploration refers to the self-understanding such as interest and capacity and relevant information gathering activities with regards to the opportunities and the obstacles in numerous environmental contexts such as school, occupation and social network.…”
Section: Discussionmentioning
confidence: 99%